Effect of pomegranate juice in modification of mutagenicity of nitrite treated aminopyrene and nitrite treated chicken extract using Ames test - Kulthida Luang-on (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2008